Is the Problem Based Learning Using Media Puzzle Effective on Students' Mathematical Connection Ability? - Linda Indiyarti Putri; Gilar Pandu Ananta; Imam Syafa'at (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractEffective mathematics learning not only teaches concepts, but also encourages students to connect the various concepts in real life. This study aims to determine the effectiveness of Problem-Based Learning (PBL) using puzzle media in improving students' mathematical connection skills in elementary school. To contribute to this problem we used two classes to test how the effect of PBL using puzzle media helps students to connect their ability to understand comparison material in grade V elementary school through quasi-experimental quantitative research with posttest-only with nonequivalent groups design. The sample in the study amounted to 54 students who were divided into a control class and an experimental class. The statistical analysis of the independent t-test results indicates a significant difference in the mathematical connection skills between students in the control and experimental classes. . The implication of this study is that the use of puzzle-assisted PBL is effective in improving students' mathematical connection skills by helping them connect mathematical concepts more practically and contextually.Keywords: Effectiveness, PBL, puzzle media, mathematical connection.Â Â AbstrakPembelajaran matematika yang efektif tidak hanya mengajarkan konsep, tetapi juga mendorong siswa untuk menghubungkan berbagai konsep tersebut dalam kehidupan nyata. Penelitian ini bertujuan untuk mengetahui efektivitas Problem-Based Learning (PBL) dengan menggunakan media puzzle dalam meningkatkan kemampuan koneksi matematis siswa di sekolah dasar. Untuk berkontribusi terhadap masalah ini kami menggunakan dua kelas untuk menguji bagaimana pengaruh PBL menggunakan media puzzle membantu siswa untuk menghubungkan kemampuan mereka dalam memahami materi perbandingan di kelas V sekolah dasar melalui penelitian kuantitatif kuasi-eksperimental dengan posttest-only with nonequivalent groups desain. Sampel pada penelitian berjumlah 54 siswa yang terbagi menjadi kelas kontrol dan kelas eksperimen. Dari hasil analisis statistik uji beda independen t-test menyatakan bahwa terdapat perbedaan yang signifikan kemampuan koneksi matematis siswa di kelas kotrol dan eksperimen. Implikasi dari penelitian ini adalah bahwa penggunaan PBL berbantuan puzzle efektif dalam meningkatkan kemampuan koneksi matematis siswa dengan membantu mereka menghubungkan konsep matematika secara lebih praktis dan kontekstual.Kata kunci: Efektivitas, PBL, media puzzle, koneksi matematis.